Naked Villany: The Fatal Attraction of Richard III and Donald Trump - Livingstone, David (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
Although no longer American President, Donald Trump still manages to upstage the current administration. An explanation for his “sinister aesthetics”, to use Joel Elliot Slotkin’s concept, can be seemingly found in developing a comparison with the eponymous king of Shakespeare’s Richard III, who masterfully employs soliloquies and asides to draw the audience and reader into his evil plots and dealings. Donald Trump also managed something similar by means of Twitter, constantly tweeting out vicious comments and insults, which kept both his followers and opponents engaged. This theatrical skill is also compared to the ‘heat’ generated by villains in professional wrestling, whose popularity is marked by how much hatred they can produce.